PENGARUH APLIKASI KOMPOS DAN LEGIN PADA PERTUMBUHAN TANAMAN SENGON DAN PERKEMBANGAN KARAT TUMOR DI AREAL YANG TERKENA DAMPAK ERUPSI GUNUNG MERAPI - , MASHLAHATUL UMAMI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi eruption in 2010 caused many ecological damages including forest and soil properties (physically, chemically, and biologically) damages around that area. Rehabilitation effort at the area could be done using Falcataria moluccana cultivation. However, F. moluccana is susceptible with gall rust disease by Uromycladium tepperianum. In critical condition such as in area which was affected by Merapi eruption caused the plants could not grow optimally and it tended to weaken the plant resistance to disease. Thus, some efforts are needed to optimize plant growth in order to improve plant resistance to disease such as using compost and leguminosae inoculants application. The objectives of this research are to evaluate the effect of compost and leguminosae inoculants application on F. moluccana growth and gall rust disease development in area which affected by Mount Merapi eruption directly and indirectly. This research was conducted in two locations those were in areas affected by Mount Merapi eruption both directly and indirectly (community forest). The research was arranged in randomized complete block design (RCBD) with 4 treatments those were compost (K) 3kg/plant, legin (L) 2 g/plant, compost and legin altogether (KL), and control. The response variables which were observed consisted of plant height, stem forming, leaves amount, and scoring on stem, leaves, and branch was to calculate gall rust disease incidence and severity. The datas were analyzed by analysis of variance. Research result showed compost, legin, compost and legin altogether application could increase plant growth about 3,2% - 7% in direct area for 9 weeks (plants 4 months of age in field) and 2,2% - 9,3% in indirect area for 8 weeks (plants 1 week of age in field). But those treatments had no effects on increasing of gall rust disease severity in indirect area (DS about 7,5% - 20,78%) and decreasing of gall rust disease severity in direct area (DS about 5,2% - 10,64%). Gall rust disease severity was more affected by environment condition and inoculum sources around the location.